THE EFFECTIVENESS OF USING TTW LEARNING MODEL ASSISTED BY "NAKOKU" SCRAPBOOK MEDIA ON NARRATIVE WRITING SKILLS - khussa'adah, Mifta; Utaminingsih, Sri; Kironoratri, Lingtang (PIONIR: JURNAL PENDIDIKAN, 2024)
This research focuses on the low writing ability of fourth-grade students at SDN 01 Bulungcangkring, particularly in narrative writing. Many students struggle to organize ideas and express them clearly in written form, which hinders their academic performance. This study aims to address this issue by evaluating the effectiveness of the Think Talk Write (TTW) learning model supported by Nakoku Scrapbook media in improving narrative writing skills. SDN 01 Bulungcangkring was chosen as it reflects common challenges in elementary-level writing skills development.This study used a Pre-Experiment design and involved 37 students from class IV SDN 01 Bulungcangkring. Data was collected using Paired Sample T-test analysis method. The results showed that the Think Talk Write (TTW) learning model supported by Nakoku Scrapbook media was effective in improving students' ability to write Indonesian narrative essays. Paired Sample T-Test statistical analysis resulted in a significant difference between the pretest score (64.6486) and posttest score (84.2162). In addition, the Sig-(2-tailed) value of 0.000 <0.05 indicates that Ho is rejected and Hi is accepted. Thus, it can be concluded that the use of Think Talk Write (TTW) learning model with Nakoku Scrapbook media has a positive impact on the narrative essay writing skills of fourth grade students of SDN 01 Bulungcangkring.Keywords: Think Talk Write, Scrapbook, Narrative Writing Skills